An increased autophagic flux contributes to the anti-inflammatory potential of urolithin A in macrophages - Boakye, Yaw Duah; Groyer, Laura; Heiss, Elke H. (Biochimica et biophysica acta, 2018)
An extract of Phyllanthus muellerianus and its constituent geraniin have been reported to exert anti-inflammatory activity in vivo. However, orally consumed geraniin, an ellagitannin, shows low bioavailability and undergoes metabolization to urolithins by gut microbiota. This study aimed at comparing geraniin and urolithin A with respect to inhibition of M1 (LPS) polarization of murine J774.1 macrophages and shedding more light on possible underlying mechanisms. Photometric, fluorimetric as well as luminescence-based assays monitored production of reactive oxygen species (ROS) and nitric oxide (NO), cell viability or reporter gene expression. Western blot analyses and confocal microscopy showed abundance and localization of target proteins, respectively. Urolithin A is a stronger inhibitor of M1 (LPS) macrophage polarization (production of NO, ROS and pro-inflammatory proteins) than geraniin. Urolithin A leads to an elevated autophagic flux in macrophages. Inhibition of autophagy in M1 (LPS) macrophages overcomes the suppressed nuclear translocation of p65 (NF-kB; nuclear factor kB), the reduced expression of pro-inflammatory genes as well as the diminished NO production brought about by urolithin A. The increased autophagic flux is furthermore associated with impaired Akt/mTOR (mammalian target of rapamycin) signaling in urolithin A-treated macrophages. Intestinal metabolization may boost the potential health benefit of widely consumed dietary ellagitannins, as suggested by side by side comparison of geraniin and urolithin A in M1(LPS) macrophages. Increased activity of the autophagic cellular recycling machinery aids the anti-inflammatory bioactivity of urolithin A. •Urolithin A shows a stronger anti-inflammatory potential than geraniin.•Urolithin A induces an elevated autophagic flux in macrophages.•Increased autophagy aids inhibition of M1 (LPS) polarization by urolithin A.•Urolithin A impairs mTOR signaling in macrophages.